213k views
4 votes
Complete each ordered pair so that it is a solution of the given linear equation.x - 2y = 3; ( ,4), (1, )

User Tajh
by
4.6k points

1 Answer

3 votes

In each of these ordered pairs we have the value of x or the value of y.

For the first one ( , 4) we can replace the value of y = 4 into the equation and solve for x:


x-2\cdot4=3
x-8=3
x=3+8=11

So the first ordered pair is (11,4)

We do something similar for the second ordered pair. We replace the value x = 1 and solve for y:


1-2y=3
1-3=2y
y=(1-3)/(2)=(-2)/(2)=-1

So the second ordered pair is (1,-1)

User DarkNeuron
by
4.8k points